2022
DOI: 10.3390/biom12091267
|View full text |Cite
|
Sign up to set email alerts
|

Amaryllidaceae Alkaloids Decrease the Proliferation, Invasion, and Secretion of Clinically Relevant Cytokines by Cultured Human Colon Cancer Cells

Abstract: Alkaloids isolated from members of the Amaryllidaceae plant family are promising anticancer agents. The purpose of the current study was to determine if the isocarbostyrils narciclasine, pancratistatin, lycorane, lycorine, crinane, and haemanthamine inhibit phenomena related to cancer progression in vitro. To achieve this, we examined the proliferation, adhesion, and invasion of cultured human colon cancer cells via MTT assay and Matrigel-coated Boyden chambers. In addition, Luminex assays were used to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 93 publications
(150 reference statements)
0
15
0
Order By: Relevance
“…This review describes the chemical and biological properties of alkaloids isolated in the last two decades from different Amaryllidaceae species. The different sections (Sections 2-4) report, in detail, the characterization of alkaloids isolated from Amaryllidaceae species diffused in regions of Southern Africa, Andean South America Among isocarbostyryls, narciclasine and pancratistatin (152 and 153, Figure 10) are amide analogues of lycorine that are very well known for they anticancer activity [6,[110][111][112]. Narciclasine (152) was isolated together with haemamthamine (5) from the bulbs of Narcissus pseudonarcissus [113].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review describes the chemical and biological properties of alkaloids isolated in the last two decades from different Amaryllidaceae species. The different sections (Sections 2-4) report, in detail, the characterization of alkaloids isolated from Amaryllidaceae species diffused in regions of Southern Africa, Andean South America Among isocarbostyryls, narciclasine and pancratistatin (152 and 153, Figure 10) are amide analogues of lycorine that are very well known for they anticancer activity [6,[110][111][112]. Narciclasine (152) was isolated together with haemamthamine (5) from the bulbs of Narcissus pseudonarcissus [113].…”
Section: Discussionmentioning
confidence: 99%
“…Among isocarbostyryls, narciclasine and pancratistatin ( 152 and 153 , Figure 10 ) are amide analogues of lycorine that are very well known for they anticancer activity [ 6 , 110 , 111 , 112 ]. Narciclasine ( 152 ) was isolated together with haemamthamine ( 5 ) from the bulbs of Narcissus pseudonarcissus [ 113 ].…”
Section: Isocarbostyryls Close To Some Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…This was confirmed by the observation of an increased PTX3 concentration due to virus activity. Interestingly, the work of Mathieu et al [71] described the usefulness of using alkaloids isolated from the Amaryllidaceae plant as anticancer agents. They revealed that those alkaloids decreed cell proliferation and PTX3 concentration (as well as VEGF and MMPs), regardless of TP53 status, which suggests the possibility of their use as multifaceted drug candidates.…”
Section: Role Of Pentraxin-3 In Gi Cancersmentioning
confidence: 99%
“…Among these compounds, amaryllidaceae alkaloids have gained attention for their potential antitumor activities. This botanical family harbors several species rich in alkaloids, such as crinine, lycorine, narciprimine, and galantamine, which have been subject to increasing interest in oncological research [1].…”
Section: Introductionmentioning
confidence: 99%